The development, implementation and evaluation of frailty assessment in oncology - O DONOVAN, ANITA (Trinity College Dublin. School of Medicine. Discipline of Radiation Therapy, 2020)
Over the last number of decades, treatment outcomes from cancer care have improved dramatically. However, these improvements have mostly benefitted younger patients, or relatively robust older adults, rather than the entire older patient population. It is well known that the evidence base surrounding oncologic management is mostly extrapolated from a younger patient cohort, or those patients who are considered fit, rather than frail or vulnerable. This is despite the fact that the majority of cancers occur in older people. Given the predicted demographic changes in many countries, there has been an increasing focus on how to more optimally manage older adults with cancer. Since these patients are currently the majority of patients affected by cancer, this area of research might well be considered to be long overdue. This doctoral thesis was designed to (i) standardise the identification, assessment and reporting of frailty in older adults with cancer, (ii) evaluate this standardised approach in a radiation oncology patient population and (iii) examine survivorship data from The Irish LongituDinal study of Aging (TILDA) in older to better elucidate the impact of frailty in follow-up care. The thesis comprises seven chapters. The first chapter discussed the background to the thesis and outlined the research aims and objectives. The second chapter provided a literature review of the field, divided into four sections i.e. (i) frailty and ageing, (ii) frailty and cancer and (iii) the role of geriatric assessment in cancer care, with a particular emphasis on existing research gaps. The review concluded that some research on the optimal method of assessing older adults with cancer has been published with regard to better integration of geriatric medicine methods. However, many different methods of assessment and frailty screening tools have been employed across different studies, making it difficult to compare the literature. In addition, a limited amount of research has occurred identifying the impact of these assessment methods in clinical practice, especially in Radiation Oncology. The third chapter aimed to address one of these research gaps, and used the Delphi methodology to gain consensus on the optimal method of geriatric assessment for older adults with cancer. The Delphi method attempts to achieve a convergence of opinion among experts on a specific topic, over a series of rounds or iterations, using a facilitated group approach. A national and international expert panel was identified to take part in this study. The fourth chapter investigated the clinical implementation of a consensus-driven approach to geriatric assessment, using the minimum dataset proceeding from the Delphi method in Chapter 3. This study took place in in Saint Luke's Radiation Oncology Network at St. James's Hospital, Dublin. This study evaluated the feasibility and acceptability of a randomised controlled trial investigating the implementation of GA in radiation oncology. The remaining chapters examine the longitudinal impact of a cancer diagnosis on older adults, in terms of relevant frailty indicators. The fifth chapter aimed to investigate to what extent community-dwelling older adults with cancer different from their non-cancer counterparts. Building on the findings of previous chapters, it sought to compare cancer survivors to their non-cancer controls, in relation to physical, cognitive, psychological and social health and wellbeing, using data from Wave 1 of TILDA. The sixth chapter aimed to investigate to what extent older adults with cancer in the community differ from their non-cancer community dwelling counterparts in relation to frailty. Frailty was operationalised using three commonly used indices, and the prevalence of each type compared. The final (seventh) chapter considered the relevance of the research data developed in this thesis, with an emphasis on original contributions to the research field and their implications for clinical practice and health policy. Also, recommendations for future research were made, arising from the research findings and limitations encountered throughout the course of this research, as well as new areas that have emerged as research priorities since the commencement of this PhD.
APPROVED
Keywords: frailty; cancer; older; geriatric assessment; geriatric oncology